2021
DOI: 10.1002/adma.202105943
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Atomic‐Scale Interactions in Nonfullerene Acceptor Organic Solar Cells with Solid‐State NMR Spectroscopy, Crystallographic Modelling, and Molecular Dynamics Simulations

Abstract: Fused‐ring core nonfullerene acceptors (NFAs), designated “Y‐series,” have enabled high‐performance organic solar cells (OSCs) achieving over 18% power conversion efficiency (PCE). Since the introduction of these NFAs, much effort has been expended to understand the reasons for their exceptional performance. While several studies have identified key optoelectronic properties that govern high PCEs, little is known about the molecular level origins of large variations in performance, spanning from 5% to 18% PCE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 74 publications
(89 reference statements)
4
52
0
Order By: Relevance
“…Molecular dynamics simulations (MDs) were conducted to estimate how the varied alkyl chains would affect the planarity and intermolecular stacking of among these NFAs. As shown in Figure S2, BTP-4Cl-C9-12, BTP-4Cl-C9-16, and BTP-4Cl-C9-20 exhibit dihedral angles of 4.9° (11.9°), 5.6° (12.0°), and 13.1° (14.4°), suggesting that elongating the alkyl chain length of NFAs could reduce their molecular planarity. The stacking and aggregation of these NFAs were further elucidated using the Polymorph module in Materials Studio .…”
mentioning
confidence: 99%
“…Molecular dynamics simulations (MDs) were conducted to estimate how the varied alkyl chains would affect the planarity and intermolecular stacking of among these NFAs. As shown in Figure S2, BTP-4Cl-C9-12, BTP-4Cl-C9-16, and BTP-4Cl-C9-20 exhibit dihedral angles of 4.9° (11.9°), 5.6° (12.0°), and 13.1° (14.4°), suggesting that elongating the alkyl chain length of NFAs could reduce their molecular planarity. The stacking and aggregation of these NFAs were further elucidated using the Polymorph module in Materials Studio .…”
mentioning
confidence: 99%
“…The SSNMR results indeed establish the molecular origins for the different optoelectronic properties, which are due to the different degrees of D-A intermix and local domain separation for the PM2:ITIC-Th and PM2: PC 61 BM blends, consistently with the recent SSNMR studies of organic semiconductors and BHJ blends. [45,[65][66][67] Next, the relative degrees of energetic order of the CT states in the blends were analyzed. Previous work has suggested that many systems which obtain high photovoltaic performance despite low energetic offsets achieve this via highly ordered domains, which facilitate both charge generation and transport.…”
Section: Discussionmentioning
confidence: 99%
“…The SSNMR results indeed establish the molecular origins for the different optoelectronic properties, which are due to the different degrees of D‐A intermix and local domain separation for the PM2:ITIC‐Th and PM2:PC 61 BM blends, consistently with the recent SSNMR studies of organic semiconductors and BHJ blends. [ 45,65–67 ]…”
Section: Discussionmentioning
confidence: 99%
“…Surface and bulk characterization techniques, as well as theoretical simulations, have been employed to understand how phase separation and other morphological features affect the PCE in these blends. [16][17][18][19][20][21][22][23] Despite the great progress of organic solar cells, the photovoltaic market is still dominated by crystalline silicon (c-Si) technologies due to the material availability, its excellent electronic charge transport properties, and PCEs >24% for large module areas >1 m 2 . Moreover, the lifetime of c-Si solar cells typically exceeds 25 years [24,25] : thermal and photochemical stability of inorganic semiconductors is in fact generally higher than that of organic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Surface and bulk characterization techniques, as well as theoretical simulations, have been employed to understand how phase separation and other morphological features affect the PCE in these blends. [ 16–23 ]…”
Section: Introductionmentioning
confidence: 99%